1989
DOI: 10.2307/3577714
|View full text |Cite
|
Sign up to set email alerts
|

Accelerated Heavy Ions and the Lens: IV. Biomicroscopic and Cytopathological Analyses of the Lenses of Mice Irradiated with 600 MeV/amu 56 Fe Ions

Abstract: The lenses of mice exposed to 600 MeV/amu iron ions were evaluated by slit-lamp biomicroscopy and cytopathological analyses. The doses ranged from 0.05 to 1.6 Gy, and the lenses were assessed at several intervals postirradiation. Cataract, the development of which is dependent on both time and dose, is significantly more advanced in all of the exposed mice when compared to the unirradiated controls. The great difference between the severity of the cataracts caused by 0.05 Gy (the lowest dose used) and those th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

1993
1993
2016
2016

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 22 publications
(8 citation statements)
references
References 26 publications
0
8
0
Order By: Relevance
“…In vitro study on the isolated intact young rat lens indicated that radiation doses as low as 100 mGy induced cataract formation [50]. At very low doses of 2 mGy to 100 mGy, exposure to 600 MeV/amu 56 Fe or medium-energy (440 keV) neutrons, 250 MeV protons, 670 MeV/amu 20 Ne, 600 MeV/amu 93 Nb, 593MeV/amu 139 La ions and 50 Co γ-rays will induce micronucleus, meridional row disorganization and various stages of lens opacification in rodents [5154]. (Table 4).…”
Section: Ldir and Ldrir-induced Bionegative Effects In Animal Modelsmentioning
confidence: 99%
“…In vitro study on the isolated intact young rat lens indicated that radiation doses as low as 100 mGy induced cataract formation [50]. At very low doses of 2 mGy to 100 mGy, exposure to 600 MeV/amu 56 Fe or medium-energy (440 keV) neutrons, 250 MeV protons, 670 MeV/amu 20 Ne, 600 MeV/amu 93 Nb, 593MeV/amu 139 La ions and 50 Co γ-rays will induce micronucleus, meridional row disorganization and various stages of lens opacification in rodents [5154]. (Table 4).…”
Section: Ldir and Ldrir-induced Bionegative Effects In Animal Modelsmentioning
confidence: 99%
“…Animal experiments have reliably shown an increased relative biological effectiveness of HZE particles for cataractogenesis when compared to X rays or 60 Co c rays, especially at low doses (16,(24)(25)(26)(27). The types of damage seen after irradiation at the tissue level are thought to be similar for HZE particles and low-LET radiation and include micronucleation, meridional row disorganization, interphase death, long-term effects on the mitotic population and focal loss of epithelial cytoarchitecture (28)(29)(30)(31).…”
Section: Discussionmentioning
confidence: 99%
“…The interphase death was suggested to be an expression of apoptosis (Broglio and Worgul 1982), although more study is required to confirm this possibility. This is extremely important inasmuch as it is predicted by the cataractotoxic load hypothesis that cataract is the result of genomic damage expressed through an altered differentiation (Worgul et al 1989 b) . Nonetheless our data are consistent with our previous finding, that FN is a dose-dependent effect .…”
Section: Discussionmentioning
confidence: 99%
“…In these studies each of the ion doses of 20, 40 and 80 cGy produced greater numbers of FNs as the LET increases up to -200 keV/pm, followed by an overall decline in number (Figure 2 a) . 1988, Worgul et al . Consistent with most of the previous work (Worgul and Merriam 1980, 1989 a) for the same LET, FN number was dose dependent (Figure 2 b also been demonstrated to be a major precataractogenic cytopathological change (Odrich et al .…”
Section: 2 Nuclear Fragmentation(fn)mentioning
confidence: 99%